Towards the Detection of UX Smells: The Support of Visualizations - Paolo Buono; Danilo Caivano; Maria Francesca Costabile; Giuseppe Desolda; Rosa Lanzilotti (IEEE Access, 2020)
Daily experiences in working with various types of computer systems show that, despite the offered functionalities, users have many difficulties, which affect their overall User eXperience (UX). The UX focus is on aesthetics, emotions and social involvement, but usability has a great influence on UX. Usability evaluation is acknowledged as a fundamental activity of the entire development process in software practices. Research in Human-Computer Interaction has proposed methods and tools to support usability evaluation. However, when performing an evaluation study, novice evaluators still have difficulties to identify usability problems and to understand their causes: they would need easier to use and possibly automated tools. This article describes four visualization techniques whose aim is to support the work of evaluators when performing usability tests to evaluate websites. Specifically, they help detect “usability smells”, i.e. hints on web pages that might present usability problems, by visualizing the paths followed by the test participants when navigating in a website to perform a test task. A user study with 15 participants compared the four techniques and revealed that the proposed visualizations have the potential to be valuable tools for novice usability evaluators. These first results should push researchers towards the development of further tools that are capable to support the detection of other types of UX smells in the evaluation of computer systems and that can be translated into common industry practices.